(untitled) (International Journal of Physiotherapy, 2015)
Background: Cerebral Palsy (CP) is a neurodevelopmental disorder caused by nonprogressive lesion in the developing brain. The early central nervous system (CNS) damage results in chronic physical disabilities and often includes sensory impairments. In addition CP is often associated with epilepsy and abnormalities of speech, vision, and intellect; it is the selective vulnerability of the brains motor systems that defines the disorder. Child friendly CIMT involves intensive targeted practice with the involved extremity coordination above and beyond their unilateral impairments. Ply Therapy is designed for active involvement of child in performing various tasks. The aim of the study is to evaluate the effectiveness of constraint induced movement therapy and play therapy to improve hand function in spastic hemiplegic cerebral palsy children. Methods: A sample of 30 patients was divided in two groups, each group having 15 children. Convenient sampling was done on the basis of base line assessment and diagnosis of their condition. Duration of the study was 3 months and data collection started at day 0 and at the end of 90 days. Children in group A wore a bivalve plaster cast on the non-involved upper extremity from shoulder to finger tips for the entire time during the session lasting for 2 hours and the plaster cast was removed at the end of the session. B group consists of 15 subjects who received play therapy. The treatment program was conducted individually and adjusted to current needs and abilities of each of the patients. Outcomes: Box and Block test, QOM scale and AOU scale. Results: It was found that there is an improvement in the hand function on application of child friendly CIMT in the patients with spastic hemiplegic cerebral palsy which was found significant using the Mann-Whitney U test (p≤0.005). Conclusion: In this study it has been found that the use of Child friendly CIMT and PLAY THERAPY produces significant improvement in hand function for young children with spastic hemiplegic cerebral palsy. However the effectiveness of child friendly CIMT is more. Improvement was considerably more than play therapy. Therefore it is concluded that child friendly CIMT is a better treatment approach then play therapy.